Histopathological description of the liver, kidneys, spleen, and flesh color of catfish (Pangasius sp.) treated with the addition of photosynthetic bacteria - Adi Suriyadin; Astutiwati; Anita Prihatini Ilyas; Muh Fahruddin; Mhd Aidil Huda. J (JURNAL MINA SAINS, 2025)
Pangasius sp. is a freshwater fish that is a favorite for the community to consume. This study aims to analyze the histopathology of catfish-given bacteria (Rhodobacter sp. and Rhodococcus sp. in aquaculture ponds against the histopathology and occurrence of yellowing in the flesh of catfish (Pangasius sp.). A randomized block design (RAK) was used for the study, with three groups:  A (0.2 mL / L), treatment B (0.5 mL / L), and C (control). The procedure for using photosynthetic bacteria is to mix each treatment dose with 1,000 mL of water and then spread it evenly in the cultivation pond. The study's results showed tissue damage to the liver, kidneys, and spleen organs, which was characterized by hemorrhage, inflammatory cell proliferation, fatty and hydropic degeneration, and Melano Macrophages Aggregate (MMA). Organ tissue damage indicates that environmental conditions or water quality are unsuitable. Unsuitable environmental conditions cause stress, dysfunction, and damage to organs. The use of photosynthetic bacteria has a better effect than without the use of photosynthetic bacteria.